The Impact of Mediation on the Settlement of Divorce Cases in Religious Courts - Kasim, Nur Mohamad; Karim, Fibriyanti (Jurnal Ius Constituendum, 2025)
The purpose is to find out the impact of the implementation of mediation and the factors that affect the success of mediation in divorce cases in Religious Courts. Mediation is a form of case settlement through Alternative Dispute Resolution. The urgency of research to resolve disputes in the divorce process in Religious Courts and help build better relationships after divorce. Using normative and empirical research types. The results of the study show that the impact of mediation on divorce is to reduce the accumulation of cases in Court, increase the satisfaction of the parties, increase time/cost efficiency, minimize conflicts, maintain privacy, encourage agreements, and build positive relationships after divorce. Factors that affect the success of divorce mediation in the Religious Court are the commitment of both parties, the competence of the mediator, support from the Court, emotional and psychological factors, and the involvement and support of third parties. In conclusion, mediation has a significant positive impact on the settlement of divorce cases in the Religious Court so mediation is an effective method and its implementation needs to be continuously improved in the Religious Court. The findings show that mediation reduces the divorce rate by increasing communication between husband and wife and resolving problems through dialogue.